Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii) complexes. Issue 54 (14th June 2021) - Dierks, Philipp; Kruse, Ayla; Bokareva, Olga S.; Al-Marri, Mohammed J.; Kalmbach, Jens; Baltrun, Marc; Neuba, Adam; Schoch, Roland; Hohloch, Stephan; Heinze, Katja; Seitz, Michael; Kühn, Oliver; et al.
Abstract : The photodynamics of two pseudoisomeric iron(ii ) complexes reveal insights into reactive metal-centred states and hot branching dynamics. A new type of reactivity by triplet energy transfer from MC states enables oxygen sensitization activity. Abstract : Two closely related Fe II complexes with 2, 6-bis(1-ethyl-1 H -1, 2, 3-triazol-4yl)pyridine and 2, 6-bis(1, 2, 3-triazol-5-ylidene)pyridine ligands are presented to gain new insights into the photophysics of bis(tridentate) iron(ii ) complexes. The [Fe(N^N^N)2 ] 2+ pseudoisomer sensitizes singlet oxygen through a MC state with nanosecond lifetime after MLCT excitation, while the bis(tridentate) [Fe(C^N^C)2 ] 2+ pseudoisomer possesses a similar 3 MLCT lifetime as the tris(bidentate) [Fe(C^C)2 (N^N)] 2+ complexes with four mesoionic carbenes.